Correlated seed failure as an environmental veto to synchronize reproduction of masting plants. Issue 1 (26th March 2018) - Bogdziewicz, Michał; Steele, Michael A.; Marino, Shealyn; Crone, Elizabeth E.
Summary: Variable, synchronized seed production, called masting, is a widespread reproductive strategy in plants. Resource dynamics, pollination success, and, as described here, environmental veto are possible proximate mechanisms driving masting. We explored the environmental veto hypothesis, which assumes that reproductive synchrony is driven by external factors preventing reproduction in some years, by extending the resource budget model of masting with correlated reproductive failure. We ran this model across its parameter space to explore how key parameters interact to drive seeding dynamics. Next, we parameterized the model based on 16 yr of seed production data for populations of red ( Quercus rubra ) and white ( Quercus alba ) oaks. We used these empirical models to simulate seeding dynamics, and compared simulated time series with patterns observed in the field. Simulations showed that resource dynamics and reproduction failure can produce masting even in the absence of pollen coupling. In concordance with this, in both oaks, among‐year variation in resource gain and correlated reproductive failure were necessary and sufficient to reproduce masting, whereas pollen coupling, although present, was not necessary. Reproductive failure caused by environmental veto may drive large‐scale synchronization without density‐dependent pollen limitation. Reproduction‐inhibiting weather events are prevalent in ecosystems, making described mechanisms likely to operate in many systems. Abstract : See also the Commentary on this article byTanentzap & Monks, 219 : 6–8 .